2013
DOI: 10.1038/nsmb.2598
|View full text |Cite
|
Sign up to set email alerts
|

Bimodal expression of PHO84 is modulated by early termination of antisense transcription

Abstract: Many S. cerevisiae genes encode antisense transcripts some of which are unstable and degraded by the exosome component Rrp6. Loss of Rrp6 results in the accumulation of long PHO84 antisense RNAs and repression of sense transcription through PHO84 promoter deacetylation. We used single molecule resolution fluorescent in situ hybridization (smFISH) to investigate antisense-mediated transcription regulation. We show that PHO84 antisense RNA acts as a bimodal switch, where continuous low frequency antisense transc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
146
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(156 citation statements)
references
References 55 publications
9
146
1
Order By: Relevance
“…If this were the case, the HXT lncRNAs may function similarly to PHO84 lncRNA that functions as a "bimodal" switch to promote different cell fates within a genetically identical population (Castelnuovo et al 2013). A third possibility is that the antisense HXT transcripts function in the cytoplasm, controlling translational efficiency to stability of the corresponding sense mRNA (Carrieri et al 2012;Pelechano and Steinmetz 2013;Wang et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…If this were the case, the HXT lncRNAs may function similarly to PHO84 lncRNA that functions as a "bimodal" switch to promote different cell fates within a genetically identical population (Castelnuovo et al 2013). A third possibility is that the antisense HXT transcripts function in the cytoplasm, controlling translational efficiency to stability of the corresponding sense mRNA (Carrieri et al 2012;Pelechano and Steinmetz 2013;Wang et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, as more efforts are put forth to decipher the role of the non-coding genome, it must be emphasized that some of these long non-coding RNAs have been detected with translating ribosomes. 88 Although no examples of lncRNAs that produce functional peptides have been documented to date, we should continue to view the term 29 Promotes induction MMF1 Mitochondrial protein YES ASP3 lncRNA 98 Upregulation ASP3 Asparagine catabolism YES PHO84 AS RNA [99][100][101] Repression PHO84 Phosphate metabolism YES SRG1 28,50,51 Repression SER3 Serine / glycine biogenesis YES PHO5 AS RNA 102 Promotes induction PHO5 Phosphate metabolism YES usURA2. 103 Repression URA2 Pyrimidine biogenesis YES usDCI1.…”
mentioning
confidence: 99%
“…10,11 It is perhaps also due to the pleasing notion that an antisense-transcribing polymerase complex might collide with and disrupt either the sense-transcribing polymerase, or else the pre-initiation complex on the sense promoter. However, Hongay et al 12 found that antisense transcription did not occur at the same time as sense transcription within the same cells, while Castelnuovo et al 13 and Nguyen et al…”
Section: Antisense Transcription Is Not a Universal Repressor Of Sensmentioning
confidence: 99%